Interactions between Public Research Organizations and Industry : Simple Additive Weighting Approach to Evaluation of Interactions - Nakamatte, Olivia; Okidi-Lating, Peter (Intl' Conference on Advances in Engineering Sciences and Applied Mathematics, 2014)
Interactions between Public Research Organizations and Industry (PRO-I interactions) are important to facilitate learning. This paper seeks to measure interactions between Uganda Industrial Research Institute (UIRI) and SMEs in Uganda. Theoretically, the study relates to the area of interactive learning between the two actors in the innovation system. The study is based on original data collected through a questionnaire administered to SME Managers between January and February 2013. Findings revealedpull efforts by SMEs and strong collaborations between UIRI and SMEs. The study concluded that the firm may be motivated to drive a strong relationship for maximum benefit since the relationship is established primarily based on the firm’s interest.